Perancangan Aplikasi Perencanaan Cakupan LTE Kabupaten Kampar - Saljuwita, Saljuwita; Sari, Linna Oktaviana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Planning for LTE coverage has several parameters that must be met according to the standards set by 3GPP and telecommunications operators. This study designed an LTE coverage planning application to determine the extent of cell coverage and the number of sites needed on a desktop basis. This application uses a frequency of 2300 MHz with the duplex TDD method and makes it easier to calculate the number of sites needed to cover all areas in Kampar Regency. The propagation model used for planning calculations is Cost-231 Hata. The research obtained results that the value of calculations in this application approached the results of manual calculations. The differences occur due to differences in rounding in the manual calculation process with rounding by the application.Keywords : LTE, coverage planning, site, Cost-231 Hata, desktop aplication